2022
DOI: 10.1200/op.22.00072
|View full text |Cite
|
Sign up to set email alerts
|

Breast Medical Oncologists' Perspectives of Telemedicine for Breast Cancer Care: A Survey Study

Abstract: PURPOSE: The COVID-19 pandemic forced rapid adoption of telemedicine (TM) for breast oncology visits in the United States, but the appropriate role of postpandemic TM is uncertain. We sought to understand physician and advance practice practitioner perspectives on the use of TM for outpatient breast cancer care through an electronically administered survey. METHODS: Breast medical oncology clinicians at two academic cancer centers and five satellite locations affiliated with the Dana Farber Cancer Institute an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…With the arrival of COVID-19, considerably more studies addressed breast cancer patients’ telemedicine experience. In general, it was altogether concluded that tele-oncology was effective, safe and that patients were highly satisfied and felt confident with their care [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Despite this overall approval, it is important to remark on the matter of the physical examination during a telehealth visit.…”
Section: Discussionmentioning
confidence: 99%
“…With the arrival of COVID-19, considerably more studies addressed breast cancer patients’ telemedicine experience. In general, it was altogether concluded that tele-oncology was effective, safe and that patients were highly satisfied and felt confident with their care [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Despite this overall approval, it is important to remark on the matter of the physical examination during a telehealth visit.…”
Section: Discussionmentioning
confidence: 99%
“…A common perception by clinicians is that telemedicine may result in missed opportunities to detect disease progression or treatment toxicity. 13,17,23,24 We found that unplanned hospitalizations were comparable between telemedicine and in-person visits (20% vs. 18%; aRR, 1.09; 95% CI, 0.92-1.28). This is consistent with reports by Hsiehchen et al, who found no association between telemedicine use and poorer patient outcomes, including oncologyrelated emergency department visits/hospitalizations, nonvisit telephone encounters, or time to treatment initiation.…”
Section: Discussionmentioning
confidence: 70%
“…24 The lack of physical examination has also raised concerns in the oncology community regarding the safety of telemedicine in patient care and the risk for missed cancer or treatment toxicity. 13,17,23,24 Furthermore, patients who lack access to or competency with video communication technology may be limited to telephone-based care, which could significantly diminish the quality of their discussions and clinical assessment. 17,[25][26][27][28][29][30] Recently published work has demonstrated discrepancies in access to telemedicine, especially videoenabled visits, among patients who are racial minorities, older, and of lower income.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCPs and patients were also accepting of receiving results via tele‐health, phone, or in‐person, supporting the concept of a flexible clinic structure to meet individual needs. Acceptance of “virtual clinics” has been reported widely in the literature, 8,11 particularly during the coronavirus disease 2019 (COVID‐19) pandemic where service model changes were rapidly implemented 12 . An Australian/European study reflecting on practices over the course of the pandemic found clinicians main concerns of “virtual clinics” related to inability to physically examine the patient, being more likely to miss a diagnosis, and reduced clinical assessment 13 .…”
Section: Discussionmentioning
confidence: 99%